Mason's world dictionary of livestock breeds, types and varieties [ - Mason, I. L. [ (Ian Lauder)] , 1914-; Porter, Valerie , 1942- (CABI, 2002)
This is a new edition of a standard reference text, and contains key breed information about cattle, sheep, pigs, goats, horses, asses and buffalo. It contains approximately 9000 entries and cross-references on breeds, sub-breeds, types, varieties, strans and lines of these species. The aim is to include all the livestock names that may be encountered in international literature. Each entry includes the current recommended English name, region or country of origin, notes on usage, followed by a brief physical description of the breed, in terms of colour/markings, horns, and coat type. There is a description of the relationship with other breeds or types, and historical notes about the origin of the breed, plus details of breed societies, and herdbooks where relevant. Finally, foreign names and synonyms are listed, to aid identification. The book has been thoroughly updated since the 4th edition was published in 1996. Revisions have been undertaken by Valerie Porter, a well-respected author of more popular works on animal breeds.